Gang Graffiti, Group Process, and Gang Violence - Hughes, Lorine A. (Journal of quantitative criminology, 2022)
Objectives Examines the neighborhood-level relationship between gang graffiti and gang violence in a large city in the western region of the US during a peak period of local gang feuds in 2014–15. Methods Bayesian Poisson log-linear mixed regression models with a spatio-temporal autoregressive process are estimated using a combination of data for N = 42,276 space–time units. Results Consistent with the view of graffiti an important means of street-level communication between gangs and an integral part of group processes associated with violence escalation and contagion, results reveal a roughly 40 to 60% increase in the expected rate of gang homicides, gang assaults, and gang firearm offenses (but not gang robberies) for each unit increase in neighborhood density of gang graffiti. Somewhat unexpectedly, the relationship with both gang homicide and gang assault was stronger for non-threatening gang graffiti than gang graffiti involving explicit threats or disrespect. Conclusions Findings suggest gang graffiti provides clear clues about local “staging grounds,” where gang status is on the line and violence is expected and easily provoked. Thus, while gangs increasingly are dissing rivals and airing beefs through music (e.g., “diss tracks”) and in cyberspace, many still occupy and defend turf and write graffiti that communicates threats to other gangs and feeds into group processes associated with violence escalation and contagion.